Marked distinctions in syntactic complexity: A case of second language university learners’ and native speakers’ syntactic constructions - Lyu, Jing; Chishti, Muhammad Ilyas; Peng, Zhibin (Frontiers in Psychology, 2022)
Existing research on syntactic complexity tends to examine diversity and complexity embedded in grammatical employments which may well be witnessed in formulations of different syntactic structures. Conceivably, the subject syntactic complexity seems to be exercised mostly by non-native speakers and writers. The present study employs pseudo-longitudinal data: essays written by undergraduate students in different levels collected at the same time. Hence, it aims at investigating the mechanism involved in the L2 production of L2 learners in terms of syntactic complexity by analyzing a corpus of non-native English-speaking learners. The research inquiry is mainly focused on investigation of significant differences in terms of syntactic complexity between writing of Japanese university students and that of native speakers, probing further into the particular dimension and level of difference. The study also traces marked variations in syntactic complexity employed by Japanese university students in different grades. Nagoya Interlanguage Corpus of English (NICE) developed by Sugiura in 2015 was employed to conduct the entire research proceedings. The corpus of the subject study comprises 339 essays written by L2 EFL learners studying in a Japanese university employing a judicious selection of quantitative measures of syntactic complexity. The results exhibited a considerable statistical difference between the writing of Japanese learners and native English writers. The findings of this study provide meaningful pedagogical implications for English teachers and textbook compilers. Japanese university students in higher grades are found to be employing more complicated and diverse syntactic structures. Conforming to the already conducted research studies with almost similar objectives, this study demonstrates the significance of using both general and more particular complexity metrics to assess syntactic development in L2. . Syntactic complexity, L2 proficiency, Genre. L2 development, academic writing quality